ERROR ANALYSIS ON THE USING BE OF SIMPLE PRESENT AND SIMPLE PAST TENSES AMONG THE SEVENTH GRADE STUDENTS OF SMP NEGERI 2 NAINGGOLAN - Sinaga, Beriman; Lumban Raja, Viator; Ginting, Fiber Yun Almanda (Kairos English Language Teaching Journal, 2020)
Grammar is the rules in a language for changing the form of words and joining them into sentences to create meaning. This research is focused on error analysis on the using BE in Simple Present and Simple Past Tenses. The purpose of this study is to find out the grammatical errors in using BE in students’ composition. In this study the writer took the the seventh grade students of SMP Negeri 2 Nainggolan in the Academic Year of 2017/2018 consisting 25 students as the sample. The data are analyzed with descriptive qualitative method. The data were identified based on kinds of errors. The kinds of errors are omission and misordering. The results of the data analysis show that there are 155 errors made by the students in their compositions. The writer concluded that omission errors 68 or 61,80% in Simple Present Tense and 49 or 51% in Simple Past Tense, misordering errors 16 or 14,60% in Simple Present Tense and 22 or 23% in Simple Past Tense. But out of category there are 28 or 23,60 redundant sentences in Simple Present Tense and 25 or 26% redundant sentences in Simple Past Tense. The writer also concluded that there are two causes of errors, namely Translation and Carelesssness. Based on the result of the research, it is suggested that the students should learn and memorize grammatical rules an teachers should give clearer explanation on grammatical rules in English.